Examining the Pearls of Islamic Education Through the History of the Prophet Adam Alaihi Salam in the Quran - Rusdi, Mikdar; Omar, Md Azmi; Omar, Norasimah; Basman, Tiara; Abdul Majid, Suhaila (Journal of Social Transformation and Regional Development, 2021)
The history of the Prophet Adam Alaihi salam became the starting point of human civilization, as the caliph and the first man of course the history and pearl of education became the focus for researchers to see further the appropriateness of the value of the caliph's education to be applied at this time. Looking at the value of the caliph's education as a prospered of the earth will lead to the creation of universal human well-being because it will return to the principles of education per the nature of human creation. The history of the prophet Adam alaihi salam is a solution that can be a reference to the model of Islamic education because basically the prophet and apostle are the first teachers (educators) sent to this earth to guide his people not to deviate from the concept of its creator. On the other hand, the history of the Prophet Adam Alaihi Salam is among the 25 prophets and messengers mentioned in the Quran and the implications of the pillars of faith that must be believed and believed to be true, in this case studying the story are part of the guidance of the pillars of faith that certainly affect the journey believers, This paper can to some extent provide a new formula in exploring the Islamic education system through the study of the history of the Prophet Adam Alaihi Salam starting from its creator, the interaction between angels and God as well as the influence and involvement of the devil in heaven as a process of maturity